KINERJA PELATIH SEKOLAH KHUSUS OLAHRAGAWANNEGERI RAGUNAN TAHUN 2011 - Imran Akhmad (Universitas Negeri Medan, 2013)
The object of this research is to find out effect of coaching knowledge, commitment, and workmotivation on the performance of the coaches of State Sport School Athletes of Ragunan. The researchwas conducted at State SMP/SMU of Ragunan, Jakarta, 2010 with n=34 all population.The research areas follow: (1) there was not an effectof coaching knowledgeon work motivation, (2) there was an effectof coachingknowledgeon the performance of the coaches, (3) there was an effect of commitment onwork motivation, (4) there was an effect of commitment on the performance of the coaches, (5) therewas an effect of work motivation on the performance of the coaches, (6) there was an effect ofcommitment on the performance of the coaches by work motivation. The conclusions of the research isthat the work motivation and performance of the coaches can be increased by improving of coachingknowledge, and commitment.